Unraveling cysteinyl leukotrienes and their receptors in inflammation through the brain-gut-lung axis - Xiao-Ru Liu; Ming Li; Qian-Qian Hao; Ya-Jie Yu; Cai Liao; Rui Yu; De-Lei Kong; Yun Wang (Virulence)
Cysteinyl leukotrienes (CysLTs), as potent lipid inflammatory mediators, play a pivotal role in systemic multi-organ inflammation and inter-organ communication through interactions with their receptors (CysLTRs). However, However, the function of CysLT3R is unclear and lacks a network of cross-organ metabolite interactions, and the clinical use of leukotriene receptor antagonists (LTRAs) has certain limitations. This review systematically synthesizes existing evidence and proposes future directions by clarifying receptor subtype specificity, optimizing targeted therapies, exploring CysLTs’ applications in neuroimmunology, and elucidating the dual roles of CysLTs in chronic inflammation. It is indicated that CysLTs activate eosinophils, mast cells, and airway tuft cells, driving type 2 immune responses and mucus secretion in the lungs, thereby exacerbating respiratory diseases such as asthma. In the nervous system, CysLTs aggravate neurodegenerative disorders like cerebral ischemia and Alzheimer’s disease by disrupting the blood-brain barrier, promoting glial activation, and inducing neuronal damage. In the gut, CysLTs regulate anti-helminth immunity via the tuft cell-ILC2 pathway and collaborate with prostaglandin D2 (PGD2) to modulate bile excretion and mucosal protection. Furthermore, CysLTs mediate communication through the gut-lung and gut-brain axes via metabolites such as succinate, contributing to cross-organ inflammatory regulation. In conclusion, this review highlights the complex roles of CysLTs in chronic inflammation, providing a theoretical foundation for precise intervention in multi-organ inflammatory diseases, which provides a theoretical framework for precision interventions in multi-organ inflammatory diseases and inspires interdisciplinary breakthroughs.